2017
DOI: 10.3389/fbioe.2017.00004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Power Delivery Timing on the Energetics and Biomechanics of Humans Wearing a Hip Exoskeleton

Abstract: A broad goal in the field of powered lower limb exoskeletons is to reduce the metabolic cost of walking. Ankle exoskeletons have successfully achieved this goal by correctly timing a plantarflexor torque during late stance phase. Hip exoskeletons have the potential to assist with both flexion and extension during walking gait, but the optimal timing for maximally reducing metabolic cost is unknown. The focus of our study was to determine the best assistance timing for applying hip assistance through a pneumati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 53 publications
5
68
0
Order By: Relevance
“…Rather than placing actuators on the exoskeleton's end-effector, researchers began placing them off-board and attached them through tethers (e.g., air hoses and Bowden cables) to streamlined exoskeleton end-effectors [45,53,54]. This approach enabled researchers to conduct high throughput, systematic studies during treadmill walking and running to determine optimal exoskeleton assistance parameters (e.g., timing and magnitude of mechanical power delivery [27,55]) for improving walking and running economy. Furthermore, the high-performance motors on recent tethered exoskeleton testbeds have relatively high torque control bandwidth that can be leveraged to render the dynamics of existing or novel design concepts [43,56].…”
Section: Leading Approaches and Technologies For Advancing Exoskeletonsmentioning
confidence: 99%
“…Rather than placing actuators on the exoskeleton's end-effector, researchers began placing them off-board and attached them through tethers (e.g., air hoses and Bowden cables) to streamlined exoskeleton end-effectors [45,53,54]. This approach enabled researchers to conduct high throughput, systematic studies during treadmill walking and running to determine optimal exoskeleton assistance parameters (e.g., timing and magnitude of mechanical power delivery [27,55]) for improving walking and running economy. Furthermore, the high-performance motors on recent tethered exoskeleton testbeds have relatively high torque control bandwidth that can be leveraged to render the dynamics of existing or novel design concepts [43,56].…”
Section: Leading Approaches and Technologies For Advancing Exoskeletonsmentioning
confidence: 99%
“…This suggests that there is an upper limit on device effectiveness as band stiffness increases, and presents the need for exploration of lowerstiffness bands in future studies. It has been shown that there are diminishing returns with increased assistance magnitude for a powered hip exoskeleton (50), as well as with assistance onset timing for the same exoskeleton (33). A similar phenomenon may be observed in the HFO, because both the magnitude and timing of its energy delivery are a function of the device con guration.…”
Section: Device Con Gurationmentioning
confidence: 70%
“…These devices aim to augment human gait through the controlled actuation of motor-driven cables or pneumatic arti cial muscles that span various joints in the lower limbs (22)(23)(24), or motors situated concentrically with joints (25,26). Studies have demonstrated that such technology can reduce muscle activation during unloaded (22,23,(27)(28)(29)(30) and loaded walking (22,31), and reduce the metabolic cost of walking in both healthy subjects (23,27,(32)(33)(34) and subjects with post-stroke hemiparesis (35,36). While promising, the costs, power demands, environmental adaptability, noisiness, and size of these devices are hurdles that must be overcome for widespread adoption of this technology (37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, with hip exoskeletons, there is a need for testbed system results (Lewis and Ferris, 2011; Lenzi et al, 2013; Young et al, 2017) to help inform the control of new autonomous systems (Giovacchini et al, 2014; Buesing et al, 2015; Seo et al, 2016; Karavas et al, 2017; Sugar et al, 2017). Ankle exoskeleton studies on testbed devices have shown that human users lower their muscle force with added ankle exoskeleton assistance to keep the total joint moment around the ankle consistent with unassisted walking (Lewis and Ferris, 2011).…”
Section: Introductionmentioning
confidence: 99%